Empirical Evidence For Sharia Financial Literacy Levels In Muslim Communities: 3T Region, Sorong, Southwest Papua - Nurul Hidayah; Nurhani Nurhani; Wisang Candra Bintari; Nugroho Dwi Prihandoko; Mitta Muthia Wangsi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Financial inclusion is positively correlated with public financial literacy, according previous literatures. National Survey of Financial Literacy and Inclusion explained that Sorong City, as one of Indonesia's 3T (Underprivileged, Frontier, and Outermost) regions, has very low sharia financial literacy, this could hinder the expansion of local sharia financial institutions. This research aims to evaluate the level of sharia financial literacy level by evaluating 5 aspects: fundamental understanding of sharia finance (FUSF), sharia insurance (SI), sharia capital market investment (ICM), sharia savings and financing (SFS), and sharia financial ethics (SFE). 100 Muslims of working age that take part in sharia financial inclusion meet the sample criteria. By using descriptive statistical analysis, the result of overall avarage score is 67%, indicates that the Muslim community in Sorong has a medium level (60-79%) sharia financial literacy, according to Chen and Volpe (1988) model. A closer look results that the medium level of literacy for the FUSF, SFS, and SFE aspects by 60%, 64%, and 73%, respectively; the high level is SI aspect by 81%, and the low level is ICM aspect by 59%. This explains why achieving sustainability in sharia financial industry still requires significant efforts to create highly financially literate society.